Contextually-Oriented Pop-Up Book Media to Improve Elementary School Students' Understanding of Balinese - I Gusti Lanang Agung Pratama Wiguna (Universitas Pendidikan Ganesha, 2024)
Students often have difficulty in understanding language concepts if only given abstract explanations without real learning media. This study aims to develop pop-up book media based on a contextual approach to improve elementary school students' language comprehension. The development model used is ADDIE, with stages of analysis, design, development, implementation, and evaluation. Data collection was carried out through observation, interviews, and media validity and practicality tests by experts and users. The results of the study showed that the developed pop-up book media received validation from material experts of 92%, media experts 93%, and language experts 91%. The practicality assessment by teachers obtained 90%, while the practicality test by students reached 98%. The effectiveness test with the Paired Sample t-Test showed a t-count value greater than the t-table, and a probability value of less than 0.05, which indicated a significant increase in students' language comprehension. Thus, pop-up book media based on a contextual approach is effective in improving elementary school students' language comprehension.